MATHEMATICAL MODELING FOR THE SIMULTANEOUS ALLOCATION AND SCHEDULING OF TOUR GUIDES: A PRACTICAL PROBLEM IN WAR TOURISM - Mohtadi , Mohammad Mahdi; Alwardi , Abbas; Pahlevanzadeh , Mohammadjavad; Fathi, Mohammad Reza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This study is a preliminary quantitative (mathematical) research conducted in war tourism. The study aims to minimize the planning, allocation, and scheduling time of "Rahian-e Noor" narrators and minimize the number of narrators. Another critical issue is to consider their preferences and competencies. The point of this study is that human capital (narrators) operates "voluntarily" without receiving any payment. Therefore, firstly, the issue of minimizing the costs of allocating salaries and benefits to human capital is ruled out. Second, some considerations must be considered in formulating constraints, including providing the narrators with sufficient rest times and, as far as possible, not forcing them to perform the tasks assigned. This study modeled a set of different constraints in a four-objective mathematical problem. This model was solved in several sample problems using two new metaheuristic algorithms, i.e., the crow search algorithm (CSA) and gray wolf optimizer (GWO). The comparison results of these two methods showed the superiority of the CSA over the GWO. Finally, a case study was conducted comparing the model output with the current situation of tour guides’ allocation, which indicated a significant improvement in different objectives.